Skull and Posterior Rib Fractures with Respiratory Failure caused by Child Abuse - Hakim, Dzulfikar Djalil Lukmanul; Noviani, Elza (Althea Medical Journal, 2017)
Background: Presence of multiple fractures suggests child abuse. Skull fractures rarely occurred but posterior rib fractures are commonly found and have high specificity as a radiological finding in child abuse. A respiratory failure can occur as a result of the damage to the osseous structure of the thorax that destabilizes the rib cage and impairs spontaneous breathing mechanism.Methods: A case report of a 6-month-old boy who presented with respiratory failure, multiple bilateral parietal and occipital bone fractures, and also fractures of right rib 5â8. The patient required ventilatory support for 9 days in the Pediatric Intensive Care Unit, Dr.HasanSadikin General Hospital.Results: The patient was on ventilatory support for 9 days, and was given antibiotics for 2 weeks. Next,Â Â the patient was referred to the High Care Unit (HCU) after the condition was stabilized, and then referred to the ward, for treatment by the Social Pediatric Division. The patient was still having issues about his foster care. Conclusions: Recognition of presence of fractures is important in early diagnosis and treatment ofÂ child abuse. [AMJ.2017;4(1):107â10]Â DOI:Â 10.15850/amj.v4n1.1030